ACUTE POST-STREPTOCOCCUS GLOMERULONEPHRITIS WITH GRADE I HYPERTENSION - Nolanda Trikanti; Etty Widyastuti (Fakultas Kedokteran Universitas Lampung, 2014)
Acute Post-Streptococcus Glomerulonephritis (APSGN) is characterized by the appearance of hematuria, proteinuria, red blood cell in the urine, swelling (edema), and hypertension with or without oligouria. It can follow beta haemolytic streptococcus bacterial infection group A in the upper respiratory tract or on the skin. Boy, 7 years old, complained of swelling in the face, legs, and genital since 5 days before entering the hospital. As long as swelling, the patient looks pale, weakness, fatigue, lethargy, and loss of appetite. A week before admission, the patient's urine was reddish. Nine days before admission, the patient had pharyngitis. In physical examination found blood pressure was 120/100 mmHg, pale skin, eyes anemic conjunctiva, swelling of palpebra, swelling of genital, swelling of lower extremity pretibia the right and left (pitting edema). Laboratory results, Hb 9.3 mg/dl, positive Anti Streptolysin Titer O (ASTO) examination, on urinalysis the urine color was red, protein 150 mg/dl and blood cryptic 250/ul. Patient was diagnosed with acute post-streptococcus glomerulonephritis with hypertension grade I. Managements were bed rest, low salt diet, supportive therapy, IVFD D5% 15 drops/min (micro), antibiotic ceftriaxone 1gr/12h, and diuretic furosemide 25mg/8h. APSGN disease has a good prognosis if treated properly. [J Agromed Unila 2014; 1(1):35-41] Keywords: acute post-streptococcus glomerulonephritis, hypertension grade I